SISTEM PENDIDIKAN DI NEGARA MALAYSIA - Abdul Wahab Syakhrani; Fathiyah Fathiyah; Fathul Janah; Fauziyyah Fauziyyah (CV. ADIBA AISHA AMIRA, 2022)
Malaysia in developing education has its own education system, of course, like other countries. Malaysia has four levels of education. The education levels include low education for 6 years, then comprehensive secondary school for 3 years, and high school for 3 years, then academic or technical education for 2 years. Then comprehensive full school for 2 years if they pass the exam, if they want to continue their education they have to take post-secondary education for 2 years. After that, only then have a Cambridge certificate that can be used to apply to the University and it is through selection.